Realization of affiliation goals, interpersonal identity development, and well-being: effects of the implicit affiliation motive among German and Zambian adolescents - Hofer, Jan; Busch, Holger; Menon, Anitha (Frontiers in Psychology, 2024)
Introduction: Across cultural contexts, success in goal realization relates to individuals’ well-being. Moreover, commitment to and successful pursuance of goals are crucial when searching for a meaningful identity in adolescence. Yet, individuals’ goals differ in how much they match their implicit motive dispositions. We hypothesized that successful pursuance of affiliation goals positively relates to commitment-related dimensions of interpersonal identity development (domain: close friends) that in turn predict adolescents’ level of well-being. However, we further assumed that the links between goal success and identity commitment are particularly pronounced among adolescents who are characterized by a high implicit affiliation motive. Methods: To scrutinize the generalizability of the assumed relationships, data were assessed among adolescents in an individualistic (Germany) and a collectivistic cultural context (Zambia). Results: Regardless of adolescents’ cultural background, we found that commitment-related dimensions of interpersonal identity development mediate the link between successful attainment of affiliation goals and well-being, particularly among adolescents with a pronounced implicit affiliation motive, that is, the strength of the implicit affiliation motive moderates the association between goal success and identity commitment. Conclusion: We discuss findings concerning universal effects of implicit motives on identity commitment and well-being.